1993
DOI: 10.1002/pola.1993.080311330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and copolymerization behavior of methacrylate dimers

Abstract: Methacrylic ester‐based dimers and oligomers were synthesized using a metal‐based catalytic chain transfer agent. Conditions were employed which maximized the yield of unsaturated dimers, and the copolymerization behavior of these dimers was investigated. The molecular weight and polymer yield were found to decrease with increasing dimer concentration in the copolymerization feeds. © 1993 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
1
40
0
1
Order By: Relevance
“…Although it is known that these macromonomers do not copolymerize with MMA, [49][50][51] copolymerization with ethyl acrylate does occur. [49,52] Therefore, copolymerization with BA is Figure 9. Reactivity ratios and 95% joint confidence intervals for the copolymerization of MMA and BA in bulk at 60 8C for different [CoBF].…”
Section: Effect Of Conversion On Cct Copolymerization Of Mma and Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that these macromonomers do not copolymerize with MMA, [49][50][51] copolymerization with ethyl acrylate does occur. [49,52] Therefore, copolymerization with BA is Figure 9. Reactivity ratios and 95% joint confidence intervals for the copolymerization of MMA and BA in bulk at 60 8C for different [CoBF].…”
Section: Effect Of Conversion On Cct Copolymerization Of Mma and Bamentioning
confidence: 99%
“…This can only mean that incorporation of macromonomers in the growing polymer chain occurs, as was also reported for MMA-homomacromer-ethyl acrylate copolymerization. [49,52] Although it is obvious that macromer copolymerization takes place at high conversions, it is expected to occur right from the start of the polymerization as well.…”
Section: Effect Of Conversion On Cct Copolymerization Of Mma and Bamentioning
confidence: 99%
“…For all other monomers oligomer incorporation was achieved. Abbey et al 81 studied the copolymerization behaviour of functional methacrylate dimers with styrene and also found that addition of dimer to a dimer ended radical does not occur.…”
Section: Reactivity and Application Of Macromonomersmentioning
confidence: 99%
“…Cacioli et al 8 showed that MMA macromers prepared via CCT copolymerized with ethyl acrylate. In more recent work, Abbey et al 9 estimated reactivity ratios for MMA dimers (made by CCT) with styrene. A number of patents 10 -12 also have been published on synthesizing comb and star polymers with macromers produced by CCT via copolymerization with acrylate monomers.…”
Section: Macromer Reactivitymentioning
confidence: 98%